Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/cjoc.202100791
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Cathode Materials for Aqueous Rechargeable Zinc‐Ion Batteries

Abstract: Comprehensive Summary Rechargeable aqueous zinc‐ion batteries (ZIBs) featuring low cost, superior performance, and environmental benignity have attracted dramatic attention as a promising alternative energy storage system to lithium‐ion batteries. Nevertheless, the development of ZIBs is still hindered by the limited selection of cathode materials due to the large solvation sheath and charge density of Zn2+. Two‐dimensional (2D) materials have attracted extraordinary attention owing to the unique layered struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 135 publications
0
9
0
Order By: Relevance
“…[131,132] It has been found that by controlling the experimental conditions such as temperature and pressure, the defect concentration and defect type can be adjusted during the process of material synthesis and growth. [133] Recently, defect engineering, including vacancy defects and edge defects, has been recognized as an effective and intriguing approach to regulate the physical and chemical properties and electronic structure of 2D nanomaterials, which has been applied broadly in electrode materials. The introduction of defects into electrode materials can not only facilitate ion diffusion and charge transfer, but also afford more storage and adsorption sites for anchoring more guest ions during electrochemical reaction process.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[131,132] It has been found that by controlling the experimental conditions such as temperature and pressure, the defect concentration and defect type can be adjusted during the process of material synthesis and growth. [133] Recently, defect engineering, including vacancy defects and edge defects, has been recognized as an effective and intriguing approach to regulate the physical and chemical properties and electronic structure of 2D nanomaterials, which has been applied broadly in electrode materials. The introduction of defects into electrode materials can not only facilitate ion diffusion and charge transfer, but also afford more storage and adsorption sites for anchoring more guest ions during electrochemical reaction process.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…The X-ray diffraction (XRD) pattern reveals that the PTFHQ has certain crystallinity compared with the majority of polymers (Figure S1b). In addition, the successful synthesis of high-purity PTFHQ could be further verified by solid-state 1 H NMR and 13 C NMR (Figure S1c-d). The scanning electron microscopy (SEM) image shows the particle-type PTFHQ with a size in the range of 0.3 to 3 μm (Figure S2), and the EDS elemental mapping reveals the even distribution of C, O, and S elements in the skeleton of PTFHQ (Figure S3).…”
Section: Resultsmentioning
confidence: 79%
“…[5][6][7][8] Among the existing energy storage systems, aqueous zinc-ion batteries (AZIBs) become a favorable choice owing to the inherent merits of Zn anodes, such as high capacity (820 mAh g À 1 ) and low redox potential (À 0.762 V against standard hydrogen electrode), as well as the high safety, non-toxic, and low cost of aqueous electrolyte. [9][10][11][12][13] At present, the research on the cathode material of AZIBs is mainly based on manganese oxides, [14][15] vanadium oxides, [16][17] and Prussian blue analogs, [18] following an inorganic intercalation/conversion mechanism, which often leads to slow kinetics and poor cycling stability due to the structure collapse and irreversible active material dissolution during the discharge/charge process. [19] Hence, it is highly desirable to design a kind of host materials with flexible structures for adaptive Zn 2 + storage/release and rapid Zn 2 + migration.…”
Section: Introductionmentioning
confidence: 99%
“…5 As an alternative to Li batteries, zinc-ion batteries (ZIBs) have gained attention with the merits of low price of Zn metal, safety in aqueous electrolytes, high theoretical capacity (volume capacity of 5855 mA h cm −3 and weight capacity of 820 mA h g −1 ), and environmental benignity. 6,7 However, dendrite growth, corrosion and the hydrogen evolution reaction…”
Section: Introductionmentioning
confidence: 99%
“…5 As an alternative to Li batteries, zinc-ion batteries (ZIBs) have gained attention with the merits of low price of Zn metal, safety in aqueous electrolytes, high theoretical capacity (volume capacity of 5855 mA h cm −3 and weight capacity of 820 mA h g −1 ), and environmental benignity. 6,7 However, dendrite growth, corrosion and the hydrogen evolution reaction (HER) occurring at the Zn anode need to be solved for the practical application of ZIBs. The exploration of novel materials, such as metal–organic frameworks (MOFs) and covalent organic frameworks (COFs), presents promising opportunities to address the challenges and achieve high-performance ZIBs.…”
Section: Introductionmentioning
confidence: 99%